TINJAUAN YURIDIS LAPORAN HASIL ANALISIS OLEH PUSAT PELAPORAN DAN ANALISIS TRANSAKSI KEUANGAN SEBAGAI ALAT BUKTI TINDAK PIDANA PENCUCIAN UANG BERDASARKAN INSTRUKSI PRESIDEN NOMOR 2 TAHUN 2017 - Fitri, Anisa; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Money Laundering is a series of activities carried out by a person or organization against illegal money, the money derived from criminal acts with the purpose of concealing or disguising the origins of the money so that it looks as legal currency. Combating money laundering is very difficult to do because it is a criminal offense which is not only extraordinary happens in one country but across the country. Combating money laundering requires the cooperation of various parties including reporting and Analysis Center for Financial Transaction as a special organization set up to combat money laundering by the investigator as law enforcement officers.Legal research is normative law research because in this study the author discusses the level of synchronization of law in order to provide a complete and clear picture of the issues examined by the authorsResults of research by the author is the first, that the Financial Transactions Reports Analysis by the Center for Financial Transaction Reporting and Analysis can not be used as evidence, just as amplifiers and consideration baan investigator. Secondly, coordination between the Center for Financial Transaction Reporting and Analysis and penyidk not implemented optimally based on Presidential Instruction No. 2 of 2017.Key words: Money-Laundering Reporting and Financial AnalisisTransaksi-Proof